PROGRAM APLIKASI PETA WISATA KABUPATEN BOYOLALI DENGAN MENGGUNAKAN GOOGLE MAPS - Sharon Yosephine; Jap Tji Beng; Wasino Wasino (Jurnal Ilmu Komputer dan Sistem Informasi, 2018)
Boyolali is located in Central Java. Tourism potential in Boyolali is not inferior to other regions because it has its own beautiful place to visit. Beside nature tourism, Boyolali also has several other tours such as agro tourism and cultural tourism. To facilitate the public in finding tourist information in Boyolali, the writer feel need to make this application program so that people who want to visit Boyolali can find out the available tourist routesThis application program is a website. The website contains tourist information and a bit about Boyolali itself. In collecting data, the writer used literature study method and documentation. While the research method used is the method of SDLC (System Developtment Life Cycle). And in making this application program, the writer using PHP and MySQL programming language for its database.